First simultaneous observations of flux transfer events at the high-latitude magnetopause by the Cluster spacecraft and pulsed radar signatures in the conjugate ionosphere by the CUTLASS and EISCAT radars - Wild, J. A.; Cowley, S. W. H.; Davies, J. A.; Khan, H.; Lester, M.; Milan, S. E.; Provan, G.; Yeoman, T. K.; Balogh, A.; Dunlop, M. W.; Fornaçon, K.-H.; Georgescu, E. (Annales Geophysicae, 2018)
Cluster magnetic field data are studied during an outbound pass through the post-noon high-latitude magnetopause region on 14 February 2001. The onset of several minute perturbations in the magnetospheric field was observed in conjunction with a southward turn of the interplanetary magnetic field observed upstream by the ACE spacecraft and lagged to the subsolar magnetopause. These perturbations culminated in the observation of four clear magnetospheric flux transfer events (FTEs) adjacent to the magnetopause, together with a highly-structured magnetopause boundary layer containing related field features. Furthermore, clear FTEs were observed later in the magnetosheath. The magnetospheric FTEs were of essentially the same form as the original "flux erosion events" observed in HEOS-2 data at a similar location and under similar interplanetary conditions by Haerendel et al. (1978). We show that the nature of the magnetic perturbations in these events is consistent with the formation of open flux tubes connected to the northern polar ionosphere via pulsed reconnection in the dusk sector magnetopause. The magnetic footprint of the Cluster spacecraft during the boundary passage is shown to map centrally within the fields-of-view of the CUTLASS SuperDARN radars, and to pass across the field-aligned beam of the EISCAT Svalbard radar (ESR) system. It is shown that both the ionospheric flow and the backscatter power in the CUTLASS data pulse are in synchrony with the magnetospheric FTEs and boundary layer structures at the latitude of the Cluster footprint. These flow and power features are subsequently found to propagate poleward, forming classic "pulsed ionospheric flow" and "poleward-moving radar auroral form" structures at higher latitudes. The combined Cluster-CUTLASS observations thus represent a direct demonstration of the coupling of momentum and energy into the magnetosphere-ionosphere system via pulsed magnetopause reconnection. The ESR observations also reveal the nature of the structured and variable polar ionosphere produced by the structured and time-varying precipitation and flow. Key words. Ionosphere (auroral ionosphere) Magentospheric physics (magnetopause, cusp and boundary layers; magnetosphere-ionosphere interactions)